Cognitive Impairment Following Acute Mild Traumatic Brain Injury - de Freitas Cardoso, Maíra Glória; Faleiro, Rodrigo Moreira; de Paula, Jonas Jardim; Kummer, Arthur; Caramelli, Paulo; Teixeira, Antônio Lúcio; de Souza, Leonardo Cruz; Miranda, Aline Silva (Frontiers in Neurology, 2019)
Patients with mild traumatic brain injury (mTBI) may present cognitive deficits within the first 24 hours after the trauma, herein called ‘acute phase’, which in turn may lead to long-term functional impairment and decrease in quality of life. There are few studies that investigate cognition in mTBI patients during the acute phase. The objectives of this study were to investigate the cognitive profile during the acute phase of patients with mTBI, whether loss of consciousness (LOC) or previous TBI influence cognition at this stage and whether education may play a potential protective role. Fifty-three patients with mTBI (aged 19 to 64 years) participated in the study. All subjects were evaluated at bedside within 24 hours post-injury. Demographical and clinical data were registered. Cognitive function was assessed with the Mini-mental state examination (MMSE), the Frontal Assessment Battery (FAB), Digit Span (working memory) and the Visual Memory Test/Brief Cognitive Battery (for episodic memory). The sample was composed mainly by men (58.5%). The mean age was 39 years-old and 64.3% of the patients had more than 8 years of education. The most common causes of mTBI were fall from own height (28.3%), aggression (24.5%) and fall from variable heights (24.5%). Regarding the cognitive profile, 26.4% had reduced global cognition as measured by the MMSE. Episodic memory impairment (13.2%) was more frequent than executive dysfunction (9.4%). No significant differences were found in cognitive performance when comparing patients with or without LOC or those with or without history of previous TBI. Patients with lower educational level had higher rates of cognitive impairment (VMT naming – 28.6% vs 4.2%; VMT immediate memory – 32% vs 4.2%; VMT learning – 39.3% vs 4.2%, all p< 0.05). In sum, we found significant cognitive impairment in the acute phase of mTBI, which was not associated with LOC or history of TBI, but appeared more frequently in patients with lower educational level.